A review on region of interest-based hybrid medical image compression algorithms - Aziz, Suhaila Ab; Sam, Suriani Mohd; Mohamed, Norliza; Daud, Salwani Mohd; Rashid, Siti Zaleha Abdul; Abas, Hafiza; Yusof, Muhammad Fathi; Dziyauddin, Rudzidatul Akmam (Telkomnika, 2020)
[...]the medical image must be compressed and sent securely through the network in the system. [...]compression has attained much attention in medical images. [...]section 5 gives the final remarks of the paper. 2.MEDICAL IMAGE COMPRESSION Medical images contain a great deal of information that is necessary for diagnosis by doctors and medical professionals. The study shows that both compressions had significant advantages and disadvantages in the field of data compression. [...]the hybrid image compression techniques have been introduced by manipulating the benefits of these two techniques to get the maximum impact [13]. [...]the region of interest (ROI) is present to resolve this issue.